Transcapsular Buttonholing of the Proximal Ulna as a Cause for Irreducible Pediatric Anterior Elbow Dislocation - Nick N. Patel; Robert W. Bruce (Case Reports in Orthopedics)
Anterior elbow dislocations in the pediatric population represent rare and sometimes difficult injuries to manage. Associated olecranon fractures are even more uncommon with limited literature existing on the topic. We present the case of a six-year-old male with a traumatic transolecranon anterior elbow fracture dislocation in whom closed reduction was prevented by buttonholing of the proximal ulna through the anterior joint capsule. This case of pediatric anterior elbow fracture dislocation provides insight into an uncommon and challenging injury complex.